A Review on the Recovery of High-Grade Critical Metals From Spent Petroleum Catalysts for Meeting the Demands of Industry 5.0 - Taz, Dilara; Ozsarac, Safak; Kursunoglu, Sait; Kursunoglu, Nilufer; Top, Soner; Altiner, Mahmut (Taylor & Francis inc, 2024)
In solvent extraction studies, various extractants, including TOPO, Alamine 308, TBP, TOA, LIX 84I, LIX 63, and Aliquat 336, were employed for the extraction and separation of vanadium, molybdenum, and cobalt from aqueous solutions of spent petroleum catalysts. Results indicated efficient metal recovery using these extractants. Furthermore, a combination of techniques, such as roasting, chemical or bioleaching, solvent extraction (SX), and precipitation, exhibited promising results in achieving comprehensive metal extraction and separation. Important discoveries have been made in the study of recovering important metals from wasted petroleum catalysts, especially with regard to attaining high metal recovery efficiencies. It is found that the recovery efficiency for manganese is 85%, cobalt is 87%, and nickel is 93%. Furthermore, it shows that this procedure may be carried out with high efficiency, with vanadium recovery surpassing 90% and molybdenum recovery efficiency above 95%. These outcomes signify a significant advancement in the field of metal extraction and separation, aligning with the principles of Industry 5.0 while emphasizing sustainability and efficiency in the production of high-tech materials for the modern era.
Altiner, Mahmut/0000-0002-7428-5999; Top, Soner/0000-0003-3486-4184; Kursunoglu, Sait/0000-0002-1680-5482
Keywords: Critical Metals; Spent Petroleum Catalyst; Leaching; Solvent Extraction; Industry 5.0